OVERPAID DAN UNDERPAID DALAM SISTEM PENGUPAHAN DAN SOLUSINYA: Studi Kasus Di PT Asia Pacific Fibers Tbk. Kaliwungu - Kiswoyo, Kiswoyo (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
This study aimed to find an alternative solution, to â€œreturn to the right pathâ€ with the wages of employees of PT Asia Pacific Fibers, Inc. which is outside the structure and pay scales (overpaid and underpaid). For employees whose wages are above the wage structure, certainly can not necessarily reduce the underpaid wages and vice versa can not be added just like that. The argument must be given a reasonable and acceptable to all parties. This argument not only for the 32 people who are outside the wage structure of wages. But it also applies to other employees. For those whose wages are above the wage structure, attempted to hold / pressed so that the gap is too wide. As for who is under the wage structure should be encouraged to enter the structure and pay scales range.The argument in question is to provide wage adjustment mechanism that is acceptable to all parties. Managing underpaid and overpaid very closely with wage adjustments each year conducted by the company. Population as well as Sample is an employee of PT Asia Pacific Fiber, Inc Kaliwungu some 32 people. The data was collected by interviews, gathering documents and questionnaires to dissect the background of the respondents. With this study, the expected structure and pay scales can be maintained so that the overpaid and underpaid does not existancy more.